Science of malaria elimination: using knowledge of bottlenecks and enablers from the Malaria Elimination Demonstration Project in Central India for eliminating malaria in the Asia Pacific region - Rajvanshi, Harsh; Singh, Mrigendra P.; Bharti, Praveen K.; Sahu, Ram Shankar; Jayswar, Himanshu; Govil, Pallavi Jain; Anvikar, Anup; Chan, Xavier Xuanhao; Chebbi, Amita; Das, Sarthak; Lal, Altaf A. (Frontiers in Public Health, 2024)
Malaria poses a major public health challenge in the Asia Pacific. Malaria Elimination Demonstration Project was conducted as a public-private partnership initiative in Mandla between State government, ICMR, and FDEC India. The project employed controls for efficient operational and management decisions. IEC campaigns found crucial in schools and communities. Capacity building of local workers emphasized for better diagnosis and treatment. SOCH mobile app launched for complete digitalization. Better supervision for Indoor Residual Sprays and optimized Long Lasting Insecticidal Nets distribution. Significant malaria cases reduction in Mandla. Insights from MEDP crucial for malaria elimination strategies in other endemic regions of the Asia Pacific.